Characterisation of the HSP70-HSP90 organising protein gene and its link to cancer - Weeks, Stacey (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
HOP (Heat shock protein 70/ Heat shock protein 90 organising protein) is a co-chaperone essential for client protein transfer from HSP70 to HSP90 within the HSP90 chaperone machine and has been found to be up-regulated in various cancers. However, minimal in vitro information can be found on the regulation of HOP expression. The aim of this study was to analyse the HOP gene structure across known orthologues, identify and characterise the HOP promoter, and identify the regulatory mechanisms influencing the expression of HOP in cancer. We hypothesized that the expression of HOP in cancer cells is likely regulated by oncogenic signalling pathways linked to cis-elements within the HOP promoter. An initial study of the evolution of the HOP gene speciation was performed across identified orthologues using Mega5.2. The evolutionary pathway of the HOP gene was traced from the unicellular organisms to fish, to amphibian and then to land mammal. The synteny across the orthologues was identified and the co-expression profile of HOP analysed. We identified the putative promoter region for HOP in silico and in vitro. Luciferase reporter assays were utilized to demonstrate promoter activity of the upstream region in vitro. Bioinformatic analysis of the active promoter region identified a large CpG island and a range of putative cis-elements. Many of the cis-elements interact with transcription factors which are activated by oncogenic pathways. We therefore tested the regulation of HOP levels by rat sarcoma viral oncogene homologue (RAS). Cancer cell lines were transfected with mutated RAS to observe the effect of constitutively active RAS expression on the production of HOP using qRT-PCR and Western Blot analyses. Additionally, inhibitors of the RAS signalling pathway were utilised to confirm the regulatory effect of mutated RAS on HOP expression. In cancer cell lines containing mutated RAS (Hs578T), HOP was up-regulated via a mechanism involving the MAPK signalling pathway and the ETS-1 and C/EBPÎ² cis-elements within the HOP promoter. These findings suggest for the first time that Hop expression in cancer may be regulated by RAS activation of the HOP promoter. Additionally, this study allowed us to determine the murine system to be the most suited genetic model organism with which to study the function of human HOP.
Keywords: Uncatalogued